Citizens' forums, and attitudes to agriculture, environment and rural priorities : Research Report by Mark Diffley Consultancy and Research and Involve /: Research Report by Mark Diffley Consultancy and Research and Involve. (2019) - Diffley, Mark; Zubairi, Sanah Saeed; Scott, Kaela; Pavlou, Andreas
No abstract available